GEOTECTONIC REGIME OF FORMATION OF THE COAL-BEARING DEPOSITS IN THE WESTERN DONETS BASIN (UKRAINE) - Ivanova, A.V.; Zaitseva, L.B.; Spirina, O.I. (Institute of Geological Sciences, NAS of Ukraine, 2018)
The geotectonic regime of the Western Donbass determined the conditions for peat accumulation, changes in phytocoenoses, formation of petrographic composition, and the nature of the transformation of organic matter, which affected the quality of coal. Hercynian tectogenesis determined the geothermal conditions of the region and the degree of coalification of organic matter, and activation of the hydrogeological regime as an additional factor of desalting of coals. In the Early Carboniferous on the swampy lagoon coast of the shallow sea, grassy vegetation was formed, which was the initial material for coals with a low and medium content of vitrinite. In the Middle  Carboniferous, the tree-like vegetation grew on the coastal-marine lowland, from which coals with a high and moderately high content of vitrinite were formed. The thickness of coal-bearing strata and the degree of coalification (metamorphism) increases in the eastern direction. A characteristic feature of coal is salinity as a result of the influence of sea water on the organic matter during peat formation. Salinity of coals decreases with increasing degree of coalification. Hercynian tectogenesis led to the erosion of Upper Paleozoic deposits with a thickness of about 3 km.